Exposure to Tick-Borne Pathogens in Cats and Dogs Infested With Ixodes scapularis in Quebec: An 8-Year Surveillance Study - Duplaix, Lauriane; Wagner, Victoria; Gasmi, Salima; Lindsay, L. Robbin; Dibernardo, Antonia; Thivierge, Karine; Fernandez-Prada, Christopher; Arsenault, Julie (Frontiers in Veterinary Science, 2021)
Cats that spend time outdoors and dogs are particularly at risk of exposure to ticks and the pathogens they transmit. A retrospective study on data collected through passive tick surveillance was conducted to estimate the risk of exposure to tick-borne pathogens in cats and dogs bitten by blacklegged ticks (Ixodes scapularis) in the province of Quebec, Canada, from 2010 to 2017. Blacklegged ticks collected from these host animals were tested by PCR for Borrelia burgdorferi sensu stricto, Borrelia miyamotoi, Anaplasma phagocytophilum, and Babesia microti. A total of 13,733 blacklegged ticks were collected from 12,547 animals. Most ticks were adult females and partially engorged. In total, 1,774 cats were infested with ticks and 22.6% and 2.7% of these animals were bitten by at least one tick infected with B. burgdorferi and A. phagocytophilium, respectively. For the 10,773 tick infested dogs, 18.4% were exposed to B. burgdorferi positive ticks while 1.9% of infested dogs were exposed to ticks infected with A. phagocytophilum. The risk of exposure of both cats and dogs to B. miyamotoi and B. microti was lower since only 1.2% and 0.1% of ticks removed were infected with these pathogens, respectively. Travelling outside of the province of Quebec prior to tick collection was significantly associated with exposure to at least one positive tick for B. burgdorferi, A. phagocytophilum and B. microti. Animals exposed to B. burgdorferi or B. miyamotoi positive tick(s) were at higher risk of being concurrently exposed to A. phagocytophilum; higher risk of exposure to B. microti was also observed in animals concurrently exposed to B. burgdorferi. The odds of dogs having B. burgdorferi antibodies were higher when multiple ticks were collected on an animal. The testing and treatment strategies used on dogs bitten by infected ticks were diverse, and misconceptions among veterinarians regarding the treatment of asymptomatic but B. burgdorferi-seropositive dogs were noted. In conclusion, our study demonstrates that cats and dogs throughout Quebec are exposed to blacklegged ticks infected with B. burgdorferi and A. phagocytophilum, and veterinarians across the province need to be aware of this potential threat to the health of pets and their owners.